Evaluation of the Compatibility of Thyroid Biopsy Results with the ACR TI-RADS Classification (Single-Center Experience): Retrospective Analytical Research. - ÖZTÜRK, Halis Harun; KÜSKÜN, Atakan; TEPE, Muzaffer Savaş (Turkiye Klinikleri Journal of Medical Sciences)
Objective: The American College of Radiology (ACR) developed the Thyroid Imaging Reporting and Data System (ACR TI-RADS), which classifies nodules into 5 categories according to their ultrasonographic features and size criteria. This study aimed to evaluate the diagnostic reliability of the ACR TI-RADS scoring system in predicting malignancy and its effectiveness in guiding biopsy decisions by comparing ultrasonographic findings with cytopathological results. Material and Methods: Thyroid nodules evaluated by ultrasonography (USG) and subjected to fine-needle aspiration biopsy (FNAB) in the Radiology Clinic between October 1, 2021, and June 1, 2023, were retrospectively analyzed. Examinations were performed using a Samsung RS85 system with a 5-14 MHz linear probe. Nodule vascularity was assessed using both grayscale and color Doppler USG prior to biopsy, and nodules were classified based on ACR TI-RADS criteria. Results: The ACR TI-RADS scoring system demonstrated good diagnostic performance for predicting malignancy in thyroid nodules, with an area under the [receiver operating characteristic (ROC)] curve (AUC) of 0.818. An optimal cut-off value of TI-RADS ≥4 was identified, yielding a sensitivity of 78.6%, specificity of 75.8%, and a negative predictive value of 93.4%. These findings indicate that the ACR TI-RADS system effectively discriminates between malignant and benign thyroid nodules, even after exclusion of the indeterminate (atypia of uncertain significance/follic-ular lesion of undetermined significance) cytology group. Conclusion: This study demonstrates that ACR TI-RADS is a reliable system for malignancy risk assessment and FNAB guidance in thyroid nodules. ROC analysis showed good discriminative performance (AUC=0.818), with a high negative predictive value (93.4%) at the TI-RADS ≥4 threshold. Solid composition, hypoechogenicity, and irregular margins were found to be the ultrasonographic features most strongly correlated with malignancy. The predominance of benign findings in ACR TI-RADS 3 nodules suggests that revising biopsy thresholds in this category may reduce unnecessary procedures.